Theoretical, computational, and experimental solutions to thermo-fluid systems select proceedings of ICITFES 2020 - Ramalingam, Velraj; Sivalingam, Murugan; Palanisamy, Muthukumar (Lecture notes in mechanical engineering, 2021)
This book presents select proceedings of the International Conference on Innovations in Thermo-Fluid Engineering and Sciences (ICITFES 2020). It covers topics in theoretical and experimental fluid dynamics, numerical methods in heat transfer and fluid mechanics, different modes of heat transfer, multiphase flow, fluid machinery, fluid power, refrigeration and air conditioning, and cryogenics. The book will be helpful to the researchers, scientists, and professionals working in the field of fluid mechanics and machinery, and thermal engineering.